Management of polyhydramnios pregnancy without risk factors: a case report - I Nyoman Hariyasa Sanjaya; Ryan Saktika Mulyana; Evert Solomon Pangkahila; Denni Prasetyo (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2020)
Introduction: Polyhydramnios is a condition in which the amount of amniotic fluid increases more than 2 litres. The causes of polyhydramnios are multifactorial, and most are idiopathic. Here we report challenging management of polyhydramnios case without apparent risk factors. Case: A 30-year-old woman G2P1001, 27-28 weeks of gestational age referred due to our tertiary health care center due to polyhydramnios. The patient chief complaint was progressively enlarged abdomen since a month ago. Her previous pregnancy, medical history and family history were unremarkable. The obstetric examination reflects the size of uterus equivalent to 36 weeks of gestational age. The fetomaternal ultrasound reveals a life, single fetus with normal heart rate and fetal movement, estimated fetal weight about 1057 grams, placenta corpus posterior grade I, Maximum Vertical Pocket 22.83 cm, no major congenital abnormalities were visible and bladder appears filled. Laboratory tests revealed blood glucose levels 90 mg/dl, Hb-A1c 5.2%, Ureum 27.30 mg/dl, Creatinine 3.39 mg/dl, and numerous leukocytes on urine sediment. Amnioreduction and fetal pulmonary maturation were conducted by Dexamethason protocol. Amnioreduction yield 1500 ml of clear, yellowish amniotic fluid. Regarding abnormality in renal function, diagnosis of Acute on Chronic Kidney Disease (ACKD were established by Internal medicine department, and the patients were given a series of ceftriaxone injection. The patient was planned for indomethacin therapy; however, Indomethacin was not available in Bali. Conclusion: Careful search for causes both from the maternal factor and fetal abnormalities can help to determine the prognosis of pregnancy. Ideally, amnioreduction, coupled with indomethacin therapy, are needed to reduce amniotic fluid, and serial monitoring of the amniotic fluid volume is required to prevent preterm labor.